SOSIALISASI BULAN IMUNISASI ANAK NASIONAL DAN EDUKASI PENTINGNYA IMUNISASI DASAR LENGKAP PADA ANAK DI DESA CIBANTENG - Denia Maulani; Diah Ayu Ristianti; Maria Yasfa (JPMUJ, 2023)
Community Service Program (KKN) is a student service activity for the community in certain areas. The KKN locations that are the main targets of community service activities are Kp. Babakan Panday RW 07 Cibanteng Village, Ciampea District, Bogor Regency. One of the important things that is difficult to get attention from the residents is the basic immunization coverage in the area which is still low. This is due to the lack of knowledge of citizens about the importance of complete basic immunization in children. Residents are worried about the side effects that arise after their child is immunized, such as fever, swelling of the skin at the injection site, the child looks tired, and cranky. The method of service carried out in Efforts to Increase Complete Basic Immunization Coverage for Children in RW 07 Cibanteng Village, Ciampea District, Bogor Regency, namely by holding a Health Seminar with the theme "Success of National Child Immunization Month Through Education on the Importance of Complete Basic Immunization in Children". With this counseling, parents can find out the benefits of immunization and the importance of complete basic immunization for children. So that it can increase the interest of the community in RW 07 to take their children to the posyandu and get basic immunizations.